Politics of Local Government Administration and the Challenges of Primary Healthcare System in Nigeria - Awofeso, Olu; Ogunne, Kingsley (Advances in Social Sciences Research Journal, 2020)
The degree of decentralization among federalist countries differs and this invariably demonstrates the dynamics of federalism in practice. The idea of federal system of government demands that there should be constitutional division of powers among the different tiers of government. To this end, in Nigeria, the federal, state and local government have their powers embedded in the constitution. However, the Nigerian constitution created much incertitude which allows local government to merely operate based on the reserved rights, disposition, prescription and discretion of the higher tiers of government. These constitutional uncertainties have no doubt created intergovernmental challenges and conflicts on areas of; tax jurisdiction, revenue allocation, fund transfers, illegal removal of government officials, autonomy, and inconsistent local government elections among others. Beyond these plaints which have been expressed in copious literature, this study tries to take further steps in analyzing how Nigeria’s intergovernmental status has impeded the operation and performance of primary healthcare system, which has invariably brought about poor health outcomes in the country, as evident in her pitiable health indicators. This work therefore establishes a nexus between local government decision space and primary healthcare systems in the country.